cis-Regulatory and Protein Evolution in Orthologous and Duplicate Genes - Castillo-Davis, Cristian I.; Hartl, Daniel L.; Achaz, Guillaume (Genome Research, 2004)
The relationship between protein and regulatory sequence evolution is a central question in molecular evolution. It is currently not known to what extent changes in gene expression are coupled with the evolution of protein coding sequences, or whether these changes differ among orthologs (species homologs) and paralogs (duplicate genes). Here, we develop a method to measure the extent of functionally relevant cis-regulatory sequence change in homologous genes, and validate it using microarray data and experimentally verified regulatory elements in different eukaryotic species. By comparing the genomes of Caenorhabditis elegans and C. briggsae, we found that protein and regulatory evolution is weakly coupled in orthologs but not paralogs, suggesting that selective pressure on gene expression and protein evolution is quite similar and persists for a significant amount of time following speciation but not gene duplication. Additionally, duplicates of both species exhibit a dramatic acceleration of both regulatory and protein evolution compared to orthologs, suggesting increased directional selection and/or relaxed selection on both gene expression patterns and protein function in duplicate genes.
10.1101/gr.2662504